2006
DOI: 10.1080/13506120500535768
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans are part of amyloid fibrils: Ultrastructural evidence in avian AA amyloid stained with cuprolinic blue and labeled with immunogold

Abstract: In domestic brown layer fowl, reactive amyloidosis of internal organs, such as liver and spleen, and of the joints is a common disorder. In a variety of amyloid types including the AA-amyloid of the chicken, in addition to amyloid fibrils, proteoglycans and glycosaminoglycans (GAGs) are found on immunohistochemistry or after extraction. The aim of the present report is to study amyloid fibrils for the ultrastructural location of GAGs by cuprolinic blue staining and immunogold labeling. Rabbit antichicken AA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Previously, Cuprolinic blue or sulfated Alcian blue have been used to show the association of sulfated GAGs with collagen fibrils (23,24). Our images on tissue confirm those studies performed previously with Cuprolinic blue or sulfated Alcian blue on tissue with amyloid-associated amyloid (36,37). In other reports, Jiang et al (38) showed that the interaction of heparin and AL LC depended on concentration and mass.…”
Section: Discussionsupporting
confidence: 80%
“…Previously, Cuprolinic blue or sulfated Alcian blue have been used to show the association of sulfated GAGs with collagen fibrils (23,24). Our images on tissue confirm those studies performed previously with Cuprolinic blue or sulfated Alcian blue on tissue with amyloid-associated amyloid (36,37). In other reports, Jiang et al (38) showed that the interaction of heparin and AL LC depended on concentration and mass.…”
Section: Discussionsupporting
confidence: 80%
“…If a patient has a visceral amyloid syndrome, even if an Ig abnormality is present, it is important to address the possibility that the amyloidosis may be secondary or familial with an incidental monoclonal gammopathy of undetermined significance . The light chain origin of an amyloid deposit can be confirmed with immunohistochemistry or an immunogold assay . Mass spectrometry can confirm the amyloid protein composition, and it is considered the standard for typing the protein subunit in amyloid deposits .…”
Section: Disease Overviewmentioning
confidence: 99%
“…If a patient has a visceral amyloid syndrome, even if an Ig abnormality is present, it is important to address the possibility that the amyloidosis may be secondary or familial with an incidental monoclonal gammopathy of undetermined significance . The light chain origin of an amyloid deposit can be confirmed with immunohistochemistry or immunogold assay . Mass spectrometry can confirm the amyloid protein composition and is considered the standard for typing the protein subunit in amyloid deposits (CME question 2).…”
Section: Disease Overviewmentioning
confidence: 99%